2020
DOI: 10.1111/1750-3841.15412
|View full text |Cite
|
Sign up to set email alerts
|

Quality control method of sterols in fermented Cordyceps sinensis based on combined fingerprint and quantitative analysis of multicomponents by single marker

Abstract: In this study, we established a new pattern for differentiating and comprehensively evaluating the quality of fermented Cordyceps sinensis based on high-performance liquid chromatography (HPLC) fingerprint analysis combined with similar analysis (SA), principal component analysis (PCA), hierarchical cluster analysis (HCA), and the quantitative analysis of multicomponents by single marker (QAMS). These methods indicated that fermented Cordyceps sinensis samples could be categorized into one class by PCA and HCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study, ALA was designated as an internal reference, and the RCFs of UFAs to be measured were calculated according to eqn (1) at the injection volumes of 2, 6, 10, 14, 18 μL. 17,33 where F s/i indicates the RCF of the internal reference ALA relative to the UFA to be measured, f s and f i represent absolute correction factors of the internal reference ALA and UFAs to be measured, respectively, C i and A i are the concentration (mg mL −1 ) and peak area (mAU) of UFAs to be measured, C s and A s are the concentration (mg mL −1 ) and peak area (mAU) of the internal reference ALA.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, ALA was designated as an internal reference, and the RCFs of UFAs to be measured were calculated according to eqn (1) at the injection volumes of 2, 6, 10, 14, 18 μL. 17,33 where F s/i indicates the RCF of the internal reference ALA relative to the UFA to be measured, f s and f i represent absolute correction factors of the internal reference ALA and UFAs to be measured, respectively, C i and A i are the concentration (mg mL −1 ) and peak area (mAU) of UFAs to be measured, C s and A s are the concentration (mg mL −1 ) and peak area (mAU) of the internal reference ALA.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies showed that nucleosides suppressed inflammation in the progress of chronic obstructive pulmonary disease ( Sun et al, 2018b ), inhibited the epithelial mesenchymal transition and protected against renal fibrosis in diabetic nephropathy ( Dong, Sun, Wei, Li, & Zhao, 2019b ). Sterols are also very important bio-functional components in fungi, and were separated or identified from C. sinensis by many researchers ( Chen et al, 2021 , Siwulski et al, 2019 , Sun et al, 2017 , Zhao et al, 2020 ). Ergosterol, a principal sterol, has been used as a useful chemical marker for evaluating the quality of C. sinensis ( Yuan, Wang, Liu, Kuang, & Zhao, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, C. sinensis, as a good functional food and drug development raw material, has been the subject of published studies, with a lot of good comments, but its edible value and medicinal value depend on its origin [17]. Different sources of C. sinensis have different sensory qualities, metabolite compositions, and flavors [18].…”
Section: Introductionmentioning
confidence: 99%